The Effect of Counseling on Discomfort During Pregnancy on Mothers' Knowledge of Changes in Pregnant Women at the Mother Health Center - Nadira Katim; Reny Retnaningsih (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Discomfort during pregnancy is a common experience resulting from physical, physiological, and psychological changes, yet it is often not well understood by pregnant women. Limited knowledge about normal bodily changes and pregnancy-related discomfort can reduce maternal comfort and increase anxiety. Counseling serves as an important educational strategy to improve pregnant women’s understanding, particularly within antenatal care services at primary health care facilities. This study aimed to examine the effect of counseling on pregnancy discomfort in improving mothers’ knowledge about changes during pregnancy. A quasi-experimental design with a one-group pretest–posttest approach was employed. The sample consisted of 50 pregnant women selected using a total sampling technique. Mothers’ knowledge levels were assessed before and after the counseling intervention using a structured questionnaire. Data analysis included univariate analysis to describe the distribution of knowledge levels and bivariate analysis using the Wilcoxon Signed Rank Test to evaluate differences before and after the intervention. The findings demonstrated a notable increase in knowledge following counseling, indicated by a shift from predominantly poor and moderate knowledge levels in the pretest to good knowledge in the posttest. Statistical analysis revealed a significant difference between pretest and posttest results (p < 0.05). In conclusion, counseling significantly improves pregnant women’s knowledge regarding pregnancy-related changes and discomfort.